Chaperone-based procedure to increase yields of soluble recombinant proteins produced in E. coli - Mogk Axel; Tomoyasu Toshifumi; Deuerling Elke; de Marco Ario; Bukau Bernd (BMC Biotechnology, 2007)
Abstract Background The overproduction of recombinant proteins in host cells often leads to their misfolding and aggregation. Previous attempts to increase the solubility of recombinant proteins by co-overproduction of individual chaperones were only partially successful. We now assessed the effects of combined overproduction of the functionally cooperating chaperone network of the E. coli cytosol on the solubility of recombinant proteins. Results A two-step procedure was found to show the strongest enhancement of solubility. In a first step, the four chaperone systems GroEL/GroES, DnaK/DnaJ/GrpE, ClpB and the small HSPs IbpA/IbpB, were coordinately co-overproduced with recombinant proteins to optimize de novo folding. In a second step, protein biosynthesis was inhibited to permit chaperone mediated refolding of misfolded and aggregated proteins in vivo. This novel strategy increased the solubility of 70% of 64 different heterologous proteins tested up to 42-fold. Conclusion The engineered E. coli strains and the two-step procedure presented here led to a remarkable increase in the solubility of a various recombinant proteins and should be applicable to a wide range of target proteins produced in biotechnology.